Psychological impacts of intimate partner violence on women - Sarmad Muhammad Soomar (International Journal on Women Empowerment, 2015)
Women are considered safe at home but many of us become intentionally unaware about the situation that Intimate Partner Violence is a harsh and unacceptable behavior that itself is exhibited by one’s own loving partner, thus making the home surroundings unsafe for women. Among all sort of violence shown by intimate partner, Physical is relatively obvious but other kinds are common too. Reasons involved behind these types of behaviors are multifactorial ranging from inequality, patriarchy and dowry to disobedience, infertility and Husbands with borderline personalities. These reasons ultimately create big disasters in women's life physically, socially and mentally. Majority of the impacts exhibited in women's life are psychological. Thus, the paper aims to highlight some major impacts of Intimate partner violence on women specially on psychological wellbeing like Depression, Posttraumatic stress disorder and Suicide, with the support of relevant literature and author's witnessed case scenario. On the basis of literature review, recommendations provided includes prevention, support, marital counseling, women's education, better health facilities for women and many others. Intimate partner violence is very common and harmful. As women are more vulnerable so these circumstances impact them at a greater extent.